Cuba a new history - Gott, Richard 1938- (Yale University Press, 2004)
The author emphasizes such little-known aspects of Cuba's history as its tradition of racism and violence, its black rebellions, the survival of its Indian peoples, and the lasting influence of Spain. The book also offers an original look at aspects of the Revolution, including Castro's relationship with the Soviet Union, military exploits in Africa, and his attempts to promote revolution in Latin America and among American blacks. In a concluding section, Gott tells the extraordinary story of the Revolution's survival in the post-Soviet years.